Genetically predicted Caspase 8 levels mediates the causal association between CD4+ T cell and breast cancer - Chen, Yanbin; Zheng, Zequn; Wang, Jinhong; Huang, Xifeng; Xie, Lei (Frontiers in Immunology, 2024)
Background: Breast cancer (BC) remains a significant contributor to female mortality globally, with inflammation and the immune system implicated in its pathogenesis. To elucidate potential causal relationships, we evaluated the relationship among 731 immune cell phenotypes and BC be at risk by using Mendelian randomization (MR), while also exploring inflammatory proteins as mediators in this association.: We obtained immune cell genome-wide association study (GWAS) summary data. (Study ID: GCST0001391 to GCST0002121) and 91 inflammatory factors (Study ID: GCST90274758 to GCST90274848) from the GWAS Catalog. Additionally, the source of BC GWAS data was obtained from the IEU Open GWAS project. (ukb-b-16890 for discovery and GCST004988 for validation). We investigated the causal link between immune cells and BC risk by employing a twosample Mendelian randomization (MR) method. Furthermore, we use a two-step MR to quantify the percentage of mediation of immune cell-BC causal effects mediated by inflammatory proteins. In addition, to ensure the robustness of immune cell-BC causal effects, we utilized another BC GWAS database (GCST004988) for validation. To make sure the causal findings were robust, a sensitivity analysis was done. Results: In both discovery and validation GWAS, Aa critical inverse correlation among between CD4+ T cells and BC risk was found using MR analysis. (Discovery: OR, 0.996; P = 0.030. Validation: OR, 0.843; P = 4.09E-07) , with with Caspase 8 levels mediating 18.9% of the reduced BC risk associated with immune cells. (Mediation proportion=a×b/c, Discovery:0.151×-0.005/-0.004=18.9%; Validation:0.151×-0.214/-0.171=18.9%) 设置了格式: 字体: 小四, 字体颜色: 自动设置 Conclusion: Our study establishes a causal connection linking among CD4+ T cells and BC, with Caspase 8 levels partially mediating this relationship. These findings enhance our genetic and molecular comprehension of BC, suggesting potential pathways for future BC immunotherapy drug development.